Religious Moderation Education at Madrasah Manbaul Uloom Malaysia - Mohammad Thoha; Hilmi Qosim Mubah; Itaanis Tianah; Rinta Ratnawati; Fatikhul Amin Abdullah; Abdul Mukhid; Busahwi (TADRIS: Jurnal Pendidikan Islam, 2025)
This article examines the implementation of religious moderation education at Madrasah Manbaul Uloom through two complementary models: formal and non-formal. The non-formal model is realized through institutional policies that encourage communal interaction in shared spaces without regard to ethnic distinctions, thereby fostering inclusivity and mutual respect. Meanwhile, the formal model is systematically integrated into the curriculum, ensuring that values of moderation are embedded within structured learning processes. Employing a qualitative research approach with a descriptive design, this study draws upon interviews with 15 students enrolled at Madrasah Manbaul Uloom, alongside three caregivers (ustadz/teachers) who served as key informants. These perspectives provide nuanced insights into both the conceptualization and practical enactment of religious moderation within the institution. The findings reveal that the values cultivated at Madrasah Manbaul Uloom encompass respect for religious diversity, recognition of ethnic plurality, and the active prevention of violence and hate speech. Collectively, these practices demonstrate how religious moderation education can be operationalized in ways that not only strengthen interfaith and interethnic harmony but also contribute to the broader goal of nurturing a peaceful and tolerant society. This study underscores the significance of integrating moderation values into both formal curricula and informal institutional practices, offering a model that may be replicated in similar educational contexts.